Gonadal Steroids and Sperm Quality in a Cohort of Relapsing Remitting Multiple Sclerosis: A Case-Control Study - D'Amico, Emanuele; Zanghì, Aurora; Burgio, Giovanni; Chisari, Clara Grazia; Condorelli, Rosita Angela; La Vignera, Sandro; Calogero, Aldo Eugenio; Patti, Francesco (Frontiers in Neurology, 2020)
Introduction: Evaluation of the hypothalamic-pituitary-testicular axis and sperm analyses are not a standard examination of patients with Relapsing-Remitting Multiple Sclerosis (RRMS). Methods: This is a prospective-case-controlled study. Patients, aged 18–55, with a confirmed diagnosis of RRMS, naïve to any DMT were enrolled. Controls were men with normal evaluation who acceded to the Andrology Center of Catania in a contemporary matched randomized fashion to the group of RRMS patients. The aim of the study is to evaluate gonadal steroids and sperm quality in men at the time of RRMS diagnosis and 12 months following the first disease modifying treatment (DMT). Results: Out of 41 patients with RRMS, 38 were included in the study (age 40.3 ± 12.3) to be compared with matched controls. Patients with RRMS showed no differences in gonadal steroids or sperm parameters, except for free testosterone (fT) plasma levels, which were lower in RRMS patients than controls (median 0.09 vs. 1.4, p < 0.0001). The correlation analyses, corrected for age and Body Mass Index, did not reveal any correlation between hormonal/sperm parameters and level of disability or disease activity at onset. Additionally, 12 months following the start of DMT, there were no differences in gonadal steroids and sperm quality compared to baseline. Conclusions: Results suggest that RRMS may not have an impact on fertility status but prospective long-term studies are needed.